Trajectory of Particulate Waste Transported by Artificial Upwelling - Caining Wen; Wei Fan; Canbo Xiao; Yonggang Zhao; Shicheng Hu; Lulu Yue; Mengjie Qu; Ying Chen (Journal of Marine Science and Engineering, 2024)
The feeding activities of fish in marine aquaculture have raised concerns about severe benthic pollution within the cage area. This paper suggests removing particulate waste from the cage area through the implementation of artificial upwelling (AU), a method likely to alleviate the organic burden within the cultivation area. A numerical model was developed to simulate AU-induced particulate matter transport under different operating conditions, with the majority of simulation results validated through flume experiments. The influence of particle characteristics, environmental conditions, and engineering parameters of AU on organic matter transport are discussed. In particular, our study offers a detailed analysis of the minimum initial upwelling velocity required to transport particulate waste to a designated distance. It also recommends situating the bottom of the cage above the maximum height of the waste plume to effectively segregate fish from the waste carried by the upwelling.